<< Chapter < Page Chapter >> Page >

Taking a derivative using leibniz’s notation, example 1

Find the derivative of y = ( x 3 x + 2 ) 5 .

First, let u = x 3 x + 2 . Thus, y = u 5 . Next, find d u d x and d y d u . Using the quotient rule,

d u d x = 2 ( 3 x + 2 ) 2

and

d y d u = 5 u 4 .

Finally, we put it all together.

d y d x = d y d u · d u d x Apply the chain rule. = 5 u 4 · 2 ( 3 x + 2 ) 2 Substitute d y d u = 5 u 4 and d u d x = 2 ( 3 x + 2 ) 2 . = 5 ( x 3 x + 2 ) 4 · 2 ( 3 x + 2 ) 2 Substitute u = x 3 x + 2 . = 10 x 4 ( 3 x + 2 ) 6 Simplify.

It is important to remember that, when using the Leibniz form of the chain rule, the final answer must be expressed entirely in terms of the original variable given in the problem.

Got questions? Get instant answers now!
Got questions? Get instant answers now!

Taking a derivative using leibniz’s notation, example 2

Find the derivative of y = tan ( 4 x 2 3 x + 1 ) .

First, let u = 4 x 2 3 x + 1 . Then y = tan u . Next, find d u d x and d y d u :

d u d x = 8 x 3 and d y d u = sec 2 u .

Finally, we put it all together.

d y d x = d y d u · d u d x Apply the chain rule. = sec 2 u · ( 8 x 3 ) Use d u d x = 8 x 3 and d y d u = sec 2 u . = sec 2 ( 4 x 2 3 x + 1 ) · ( 8 x 3 ) Substitute u = 4 x 2 3 x + 1 .
Got questions? Get instant answers now!
Got questions? Get instant answers now!

Use Leibniz’s notation to find the derivative of y = cos ( x 3 ) . Make sure that the final answer is expressed entirely in terms of the variable x .

d y d x = −3 x 2 sin ( x 3 )

Got questions? Get instant answers now!

Key concepts

  • The chain rule allows us to differentiate compositions of two or more functions. It states that for h ( x ) = f ( g ( x ) ) ,
    h ( x ) = f ( g ( x ) ) g ( x ) .

    In Leibniz’s notation this rule takes the form
    d y d x = d y d u · d u d x .
  • We can use the chain rule with other rules that we have learned, and we can derive formulas for some of them.
  • The chain rule combines with the power rule to form a new rule:
    If h ( x ) = ( g ( x ) ) n , then h ( x ) = n ( g ( x ) ) n 1 g ( x ) .
  • When applied to the composition of three functions, the chain rule can be expressed as follows: If h ( x ) = f ( g ( k ( x ) ) ) , then h ( x ) = f ( g ( k ( x ) ) g ( k ( x ) ) k ( x ) .

Key equations

  • The chain rule
    h ( x ) = f ( g ( x ) ) g ( x )
  • The power rule for functions
    h ( x ) = n ( g ( x ) ) n 1 g ( x )

For the following exercises, given y = f ( u ) and u = g ( x ) , find d y d x by using Leibniz’s notation for the chain rule: d y d x = d y d u d u d x .

y = 3 u 6 , u = 2 x 2

Got questions? Get instant answers now!

y = 6 u 3 , u = 7 x 4

18 u 2 · 7 = 18 ( 7 x 4 ) 2 · 7

Got questions? Get instant answers now!

y = sin u , u = 5 x 1

Got questions? Get instant answers now!

y = cos u , u = x 8

sin u · −1 8 = sin ( x 8 ) · −1 8

Got questions? Get instant answers now!

y = 4 u + 3 , u = x 2 6 x

8 x 24 2 4 u + 3 = 4 x 12 4 x 2 24 x + 3

Got questions? Get instant answers now!

For each of the following exercises,

  1. decompose each function in the form y = f ( u ) and u = g ( x ) , and
  2. find d y d x as a function of x .

y = ( 3 x 2 + 1 ) 3

a. u = 3 x 2 + 1 ; b. 18 x ( 3 x 2 + 1 ) 2

Got questions? Get instant answers now!

y = ( x 7 + 7 x ) 7

a. f ( u ) = u 7 , u = x 7 + 7 x ; b. 7 ( x 7 + 7 x ) 6 · ( 1 7 7 x 2 )

Got questions? Get instant answers now!

y = csc ( π x + 1 )

a. f ( u ) = csc u , u = π x + 1 ; b. π csc ( π x + 1 ) · cot ( π x + 1 )

Got questions? Get instant answers now!

y = −6 sin −3 x

a. f ( u ) = −6 u −3 , u = sin x , b. 18 sin −4 x · cos x

Got questions? Get instant answers now!

For the following exercises, find d y d x for each function.

y = ( 3 x 2 + 3 x 1 ) 4

Got questions? Get instant answers now!

y = ( 5 2 x ) −2

4 ( 5 2 x ) 3

Got questions? Get instant answers now!

y = ( 2 x 3 x 2 + 6 x + 1 ) 3

6 ( 2 x 3 x 2 + 6 x + 1 ) 2 ( 3 x 2 x + 3 )

Got questions? Get instant answers now!

y = ( tan x + sin x ) −3

−3 ( tan x + sin x ) −4 · ( sec 2 x + cos x )

Got questions? Get instant answers now!

y = sin ( cos 7 x )

−7 cos ( cos 7 x ) · sin 7 x

Got questions? Get instant answers now!

y = cot 3 ( 4 x + 1 )

−12 cot 2 ( 4 x + 1 ) · csc 2 ( 4 x + 1 )

Got questions? Get instant answers now!

Let y = [ f ( x ) ] 3 and suppose that f ( 1 ) = 4 and d y d x = 10 for x = 1 . Find f ( 1 ) .

Got questions? Get instant answers now!

Let y = ( f ( x ) + 5 x 2 ) 4 and suppose that f ( −1 ) = −4 and d y d x = 3 when x = −1 . Find f ( −1 )

10 3 4

Got questions? Get instant answers now!

Let y = ( f ( u ) + 3 x ) 2 and u = x 3 2 x . If f ( 4 ) = 6 and d y d x = 18 when x = 2 , find f ( 4 ) .

Got questions? Get instant answers now!

[T] Find the equation of the tangent line to y = sin ( x 2 ) at the origin. Use a calculator to graph the function and the tangent line together.

y = −1 2 x

Got questions? Get instant answers now!

[T] Find the equation of the tangent line to y = ( 3 x + 1 x ) 2 at the point ( 1 , 16 ) . Use a calculator to graph the function and the tangent line together.

Got questions? Get instant answers now!

Find the x -coordinates at which the tangent line to y = ( x 6 x ) 8 is horizontal.

x = ± 6

Got questions? Get instant answers now!

[T] Find an equation of the line that is normal to g ( θ ) = sin 2 ( π θ ) at the point ( 1 4 , 1 2 ) . Use a calculator to graph the function and the normal line together.

Got questions? Get instant answers now!

For the following exercises, use the information in the following table to find h ( a ) at the given value for a .

x f ( x ) f ( x ) g ( x ) g ( x )
0 2 5 0 2
1 1 −2 3 0
2 4 4 1 −1
3 3 −3 2 3

h ( x ) = f ( g ( x ) ) ; a = 0

10

Got questions? Get instant answers now!

h ( x ) = g ( f ( x ) ) ; a = 0

Got questions? Get instant answers now!

h ( x ) = ( x 4 + g ( x ) ) −2 ; a = 1

1 8

Got questions? Get instant answers now!

h ( x ) = ( f ( x ) g ( x ) ) 2 ; a = 3

Got questions? Get instant answers now!

h ( x ) = f ( x + f ( x ) ) ; a = 1

−4

Got questions? Get instant answers now!

h ( x ) = ( 1 + g ( x ) ) 3 ; a = 2

Got questions? Get instant answers now!

h ( x ) = g ( 2 + f ( x 2 ) ) ; a = 1

−12

Got questions? Get instant answers now!

h ( x ) = f ( g ( sin x ) ) ; a = 0

Got questions? Get instant answers now!

[T] The position function of a freight train is given by s ( t ) = 100 ( t + 1 ) −2 , with s in meters and t in seconds. At time t = 6 s, find the train’s

  1. velocity and
  2. acceleration.
  3. Using a. and b. is the train speeding up or slowing down?

a. 200 343 m/s, b. 600 2401 m/s 2 , c. The train is slowing down since velocity and acceleration have opposite signs.

Got questions? Get instant answers now!

[T] A mass hanging from a vertical spring is in simple harmonic motion as given by the following position function, where t is measured in seconds and s is in inches:

s ( t ) = −3 cos ( π t + π 4 ) .

  1. Determine the position of the spring at t = 1.5 s.
  2. Find the velocity of the spring at t = 1.5 s.
Got questions? Get instant answers now!

[T] The total cost to produce x boxes of Thin Mint Girl Scout cookies is C dollars, where C = 0.0001 x 3 0.02 x 2 + 3 x + 300 . In t weeks production is estimated to be x = 1600 + 100 t boxes.

  1. Find the marginal cost C ( x ) .
  2. Use Leibniz’s notation for the chain rule, d C d t = d C d x · d x d t , to find the rate with respect to time t that the cost is changing.
  3. Use b. to determine how fast costs are increasing when t = 2 weeks. Include units with the answer.

a. C ( x ) = 0.0003 x 2 0.04 x + 3 b. d C d t = 100 · ( 0.0003 x 2 0.04 x + 3 ) c. Approximately $90,300 per week

Got questions? Get instant answers now!

[T] The formula for the area of a circle is A = π r 2 , where r is the radius of the circle. Suppose a circle is expanding, meaning that both the area A and the radius r (in inches) are expanding.

  1. Suppose r = 2 100 ( t + 7 ) 2 where t is time in seconds. Use the chain rule d A d t = d A d r · d r d t to find the rate at which the area is expanding.
  2. Use a. to find the rate at which the area is expanding at t = 4 s.
Got questions? Get instant answers now!

[T] The formula for the volume of a sphere is S = 4 3 π r 3 , where r (in feet) is the radius of the sphere. Suppose a spherical snowball is melting in the sun.

  1. Suppose r = 1 ( t + 1 ) 2 1 12 where t is time in minutes. Use the chain rule d S d t = d S d r · d r d t to find the rate at which the snowball is melting.
  2. Use a. to find the rate at which the volume is changing at t = 1 min.

a. d S d t = 8 π r 2 ( t + 1 ) 3 b. The volume is decreasing at a rate of π 36 ft 3 /min.

Got questions? Get instant answers now!

[T] The daily temperature in degrees Fahrenheit of Phoenix in the summer can be modeled by the function T ( x ) = 94 10 cos [ π 12 ( x 2 ) ] , where x is hours after midnight. Find the rate at which the temperature is changing at 4 p.m.

Got questions? Get instant answers now!

[T] The depth (in feet) of water at a dock changes with the rise and fall of tides. The depth is modeled by the function D ( t ) = 5 sin ( π 6 t 7 π 6 ) + 8 , where t is the number of hours after midnight. Find the rate at which the depth is changing at 6 a.m.

~ 2.3 ft/hr

Got questions? Get instant answers now!

Questions & Answers

how to find a limit algebraically
Apple Reply
Follow the rules of limit and evaluate
Dadi
what is Cale nation
Musu Reply
its probably a football leage in kentucky
Luis
what are the 12 theorem of limits
Xhyna Reply
I don't understand the set builder nototation like in this case they've said numbers greater than 1 but less than 5 is there a specific way of reading {x|1<x<5} this because I can't really understand
Ivwananji Reply
x is equivalent also us 1...
Jogimar
a < x < b means x is between a and b which implies x is greater than a but less than b.
Bruce
alright thanks a lot I get it now
Ivwananji
I'm trying to test this to see if I am able to send and receive messages.
Bruce Reply
👍
Jogimar
It's possible
joseph
yes
Waidus
Anyone with pdf tutorial or video should help
joseph
maybe.
Jogimar
hellow gays. is it possible to ask a mathematical question
Michael
A good book
Habib
What is the derivative of 3x to the negative 3
Wilbur Reply
-3x^-4
Mugen
that's wrong, its -9x^-3
Mugen
Or rather kind of the combination of the two: -9x^(-4) I think. :)
Csaba
-9x-4 (X raised power negative 4=
Simon
-9x-³
Jon
I have 50 rupies I spend as below Spend remain 20 30 15 15 09 06 06 00 ----- ------- 50 51 why one more
Muhsin Reply
Pls Help..... if f(x) =3x+2 what is the value of x whose image is 5
Akanuku Reply
f(x) = 5 = 3x +2 x = 1
x=1
Bra
can anyone teach me how to use synthetic in problem solving
Mark
x=1
Mac
can someone solve Y=2x² + 3 using first principle of differentiation
Rachael Reply
ans 2
Emmanuel
Yes ☺️ Y=2x+3 will be {2(x+h)+ 3 -(2x+3)}/h where the 2x's and 3's cancel on opening the brackets. Then from (2h/h)=2 since we have no h for the limit that tends to zero, I guess that is it....
Philip
Correct
Mohamed
thank you Philip Kotia
Rachael
Welcome
Philip
g(x)=8-4x sqrt of 3 + 2x sqrt of 8 what is the answer?
Sheila
hi
px
hi
Gajji
helo
Tufail
g(x)=8-4x sqrt of 3 + 2x sqrt of 8 what is the answer? what require to you .require give me?
Tufail
Hello
Agyei
I have no idea what these symbols mean can it be explained in English words
bill Reply
which symbols
John
How to solve lim x squared two=4
Musisi Reply
why constant is zero
Saurabh Reply
Rate of change of a constant is zero because no change occurred
Highsaint
What is the derivative of sin(x + y)=x + y ?
Frendick Reply
_1
Abhay
How? can you please show the solution?
Frendick
neg 1?
muhammad
Solution please?😪
Frendick
find x^2 + cot (xy) =0 Dy/dx
Miss-K Reply
Continuos and discontinous fuctions
Amoding Reply
Practice Key Terms 1

Get the best Calculus volume 1 course in your pocket!





Source:  OpenStax, Calculus volume 1. OpenStax CNX. Feb 05, 2016 Download for free at http://cnx.org/content/col11964/1.2
Google Play and the Google Play logo are trademarks of Google Inc.

Notification Switch

Would you like to follow the 'Calculus volume 1' conversation and receive update notifications?

Ask